The Life of Ramanandi Centres in Varanasi - Bevilacqua, Daniela (Religions of South Asia, 2021)
The Ramanandi sampraday is a Vaisnava religious order supposedly formed by Ramanand in Varanasi in the fifteenth century. The sampraday, nevertheless, primarily developed and spread in the north-west of India, and Ramanandi centres (re)appeared in Varanasi around the nineteenth century. Although renowned for its Saiva temples and ascetics, Varanasi, indeed, also manifests a Vaisnava nature. Referring to an inquiry on the ascetic groups present in the city led by anthropologists Sinha and Saraswati in the 1960s, this article focuses its attention on Ramanandis centres in the twenty-first century. Following the list of places provided by the two scholars, using local traditions and ethnographic data, the article provides glimpses into the life of ‘subaltern’ Ramanandi temples and asrams, showing how today the survival of local religious centres depends on the support of lay people, who may be attracted by devotion to specific places, but mostly by the charisma and the activities of their leaders and the religious community they are able to create.